Prevalence of dental anomalies in different cleft lip and palate groups: A survey - Ritu Sanjaykumar Somani; Dolly Patel; Mahesh Jain (Wolters Kluwer Medknow Publications, 2022)
Introduction: Patients with orofacial clefts are usually associated with various dental anomalies. These dental aberrations pose a clinical challenge in treatment planning. Thus, this investigation intends to find the prevalence rate of different types of dental anomalies and their correlation among nonsyndromic cleft patients. Methodology: Orthodontic records of 129 cleft patients classified into different cleft groups were assessed to evaluate the presence of different dental anomalies. Results: The most frequent dental anomaly found in Cleft patients was rotations followed by maxillary lateral incisor agenesis with a prevalence rate of 90.4% and 59.2%, respectively. Maxillary second premolar agenesis, peg-shaped laterals, mandibular second premolar agenesis, and supernumerary teeth showed prevalence rates as 25%, 21%, 7%, and 5%, respectively. There were significant differences in the overall distribution of maxillary lateral incisor agenesis and rotations between patients with Unilateral Cleft Lip and Cleft Palate, Bilateral Cleft Lip and Cleft Palate, Cleft Lip (CL), and Isolated Cleft Palate (ICP). Conclusion: There is a high prevalence of dental anomalies like rotations and maxillary lateral incisor agenesis in different CL and palate patients, which were statistically significant. The presence of such anomalies can deteriorate the already existing functional problem and hence, the study of these anomalies and their treatment is an important step in the rehabilitation of such patients.